Adab Murid Terhadap Guru dalam Pandangan KH. Hasyim Asy'ary - Fauseh, Fauseh (Mahad Aly Al Fithrah Press, 2022)
In the global era like today, one of the problems we face the problem of moral decadence. This problem not only affects children or adolescents but also occurs in parents, especially teachers. The teacher is a figure who is widely exemplified by all his actions not only by his students but also by many people. There is one opinion that says that students can forget the words (explanations) of the teacher, but they will never forget their attitudes and deeds. Therefore, teachers must display commendable attitudes that are worthy of exemplary. Courtesy can be terminologically identified that courtesy can be interpreted as good ethics, commendable behavior, educated soul and morals, discipline to be a civilized person, moral or morality, affection, ethics, character, values, and technically-practical characters can also be interpreted as manners and manners. In this case came a new idea to improve the morals of the teacher. Many experts formulate as understanding or thinking about the morals of students towards the teacher. Among them is thought of Hadrotus Shaykh KH. Hashim Ash'ary. His thoughts should be used as a reference for students to always be in the right corridor. According to KH. Hashim Asy'ary students must choose the right teacher who has been informed of his skills and intelligence, has a teacher's soul, authoritative and has high self-esteem and awake, in addition to also having a good teaching system and easy description to understand.